2019
DOI: 10.1111/ene.14108
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson disease

Abstract: Parkinson disease (PD) is the most common neurodegenerative movement disorder. In Europe, prevalence and incidence rates for PD are estimated at approximately 108–257/100 000 and 11–19/100 000 per year, respectively. Risk factors include age, male gender and some environmental factors. The aetiology of the disease in most patients is unknown, but different genetic causes have been identified. Although familial forms of PD account for only 5%–15% of cases, studies on these families provided interesting insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
760
0
48

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,055 publications
(814 citation statements)
references
References 125 publications
6
760
0
48
Order By: Relevance
“…Other FDA approved treatments for PD are predominantly focused on increasing or substituting for low levels of DA to manage tremors and irregular movements: DA agonists directly stimulate the DA receptors, monoamine oxidase B inhibitors prolong DA stimulation by decreasing DA breakdown, and catechol-O-methyl transferase inhibitors delay the breakdown of L-DOPA. 10 Non-dopaminergic treatments include anticholinergics, adenosine 2A antagonists, and a drug that is reported to act via multiple mechanisms to exert anti-Parkinsonian effects (amantadine). 20 These FDA-approved drugs can be used as alternatives to L-DOPA, in addition to L-DOPA, or in combination with one another.…”
Section: Current Drug Landscape and Kinases As The Futurementioning
confidence: 99%
See 2 more Smart Citations
“…Other FDA approved treatments for PD are predominantly focused on increasing or substituting for low levels of DA to manage tremors and irregular movements: DA agonists directly stimulate the DA receptors, monoamine oxidase B inhibitors prolong DA stimulation by decreasing DA breakdown, and catechol-O-methyl transferase inhibitors delay the breakdown of L-DOPA. 10 Non-dopaminergic treatments include anticholinergics, adenosine 2A antagonists, and a drug that is reported to act via multiple mechanisms to exert anti-Parkinsonian effects (amantadine). 20 These FDA-approved drugs can be used as alternatives to L-DOPA, in addition to L-DOPA, or in combination with one another.…”
Section: Current Drug Landscape and Kinases As The Futurementioning
confidence: 99%
“…been thought to be mainly composed of alpha-synuclein and ubiquitin. 10 A recent study, however, demonstrated that Lewy bodies are composed of a membranous medley rather than protein fibrils, which includes membrane fragments, lipids, and other cellular material. 11 More recently, studying immune dysregulation in PD has attracted increased interest as activated microglia and T cells have been found in the SN of PD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson's disease (PD) is the second most common neurodegenerative disease in the whole world (Balestrino and Schapira, 2019). PD mainly affects the locomotor system by degenerating the neuron, finally leading to severe disability (Balestrino and Schapira, 2019). The clinical criteria for diagnosis of PD depend mainly on the observation of movement disorders such as cogwheel rigidity, bradykinesia, resting tremor, etc.…”
Section: Introduction Of Parkinson's Disease (Pd) and Other Neurodegementioning
confidence: 99%
“…The clinical criteria for diagnosis of PD depend mainly on the observation of movement disorders such as cogwheel rigidity, bradykinesia, resting tremor, etc. (Balestrino and Schapira, 2019). In the dopaminergic neurons, phosphor-α-synuclein molecules can aggregate with one another easily to form Lewy body, and these degenerative dopaminergic neurons lose the function of expressing dopamine, finally leading to the damage of the motor cortex and movement disorders (Ikenaka et al, 2019).…”
Section: Introduction Of Parkinson's Disease (Pd) and Other Neurodegementioning
confidence: 99%